ATTACHMENT STYLE IN CHILDREN WITH CHRONIC DISEASES: A COMPREHENSIVE REVIEW - Virgínia Menezes Coutinho; Bianca Arruda Manchester de Queiroga; Rafaela Cristina de Souza (Sociedade de Pediatria de São Paulo, 2020)
ABSTRACT Objective: To investigate how attachment style has been studied in children with chronic disease in the scientific literature, and what repercussions this attachment has on this population. Data sources: An integrative review of the literature was carried out from a survey in the LILACS, MEDLINE and SciELO databases, including original national and international publications in Portuguese, Spanish and English from 2007 to 2018, using the descriptors "apego" and "criança" in the Health Sciences Descriptors (DeCS), and "attachment" and "children" for the Medical Subject Headings (MeSH). Sixteen (16 articles) were obtained for the sample analysis. Data synthesis: The chronic diseases found in the research were neurobehavioral disorders such as attention deficit hyperactivity disorder (ADHD) and autism, childhood obesity, and chronic migraine. The predominant attachment style was insecurity, which could compromise the biopsychosocial development of the child. Conclusions: The type of attachment between child and primary caregiver may be considered a protective or risk factor for child development. Considering this premise, it is important to equip/inform families based on dialogic educational practices, in which professionals create opportunities and means for families to develop their skills and competencies, and acquire resources which meet the child's needs. It is important that this professional helps the family to build secure bases for their child with chronic disease, understanding that the main focus for promoting child development is in the family unit.